ANALISA PEMASANGAN SISTEM PENGGERAK PADA KAPAL CRANE BARGE DENGAN PROPULSI ELEKTRIK - Farrel Chandra Mukti; Eko Julianto; Abdul Gafur (Politeknik Perkapalan Negeri Surabaya, 2020)
A Crane barge ship is a ship designed specifically to have a crane on deck. The function of thisship is to unload coal/bulk cargo at the mid-sea, which is to go the middle of the sea this sip must be towedby Tugboat. This research will discuss the analysis of the propulsion system using electric propulsion withazimuth thruster propeller. In this study the calculation is the resistance of the ship, power requirement bythe ship, selecting of a propeller, electrical system. The calculation resistance of the ship using maxsurfresistance software, before simulation the model 3D of ship design in maxsurf modeler. Then if theresistance value is determined can be used to calculate the power of electric motor requirement as theprimer mover of the ship. Then the result of these calculations can be selected as the propeller. Based onthe calculation result, the value of the ship resistance is 1555,95 kW when the ship used 4 azimuth thruster,so the resistance value is 388,987 kN. The power of the electricity needs to supply power to motor electricas the primer mover is 4632 kW. The Selection of propeller used is a product from thrustmaster which hasa thrust is 529 kN with a diameter propeller is 2.99 meters.